Lithocarpus pacoensis (Fagaceae) a New Species from Hoa Binh Province, Vietnam - Ngoc, Nguyen Van (2023)
Lithocarpus pacoensis Ngoc & Son from Hoa Binh province, Northern Vietnam, was described and illustrated. The new species is similar to Lithocarpus komtumensis A. Camus and Lithocarpus laoticus (Hickel & A. Camus) A.Camus in having long petioles; big cupules, usually clustered in sets of three, flat apical, nearly completely enclosing the nut; nut subglobose apex rounded or flat; scar covering 2/3 to most of the nut, convex. But the new species significantly differs from L. kontumensis and L. laoticus in having bigger leaf blades, longer petiole, much bigger cupule and nut, much more number of secondary veins, and shorter infructescences. The morphological description, comparison with related species, photographs, and preliminary conservation status assessment of the new species are also provided.